Implementation of CHSE Health Protocol in Increasing Guest Confidence at Hotel Gran Melia Jakarta - Hanni Fathia; Liliana Dewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The hotel business is one part of the tourism business that has been most disadvantaged by the coronavirus. Many hotels forced to close because there were no more guests and the food and meeting business was no longer filled. CHSE promotes a clean, healthy, safe and friendly environment. The current guset trend is to choose a clean and safe place from covid-19. The purpose of this study was to determine the implementation of the CHSE health protocol in hotels, the level of trust of guest to stay, and the factors that influence the performance of CHSE. The research method uses a qualitative approach. The infromants in. The data analysis technique used is qualitative data analysis, carried out interactively through data reduction, data display, and verification. Result showed that the implemntation of the CHSE health protocol was quite siccessful in increasing guest confidence to stay. Guest have confidence that the CHSE certificate displayed at the hotel and other promotional media guarantees that the transmission of covid-19 can be eliminated. Internal factors such as the support of health facilities and infrastructure and external factors, namely the cooperation and coordination between related parties, public policies and customer awareness greatly affect the implementation of the CHSE Health Protocol.